Adopsi Teknologi Pengendalian Hama Terpadu dalam Meningkatkan Efisiensi dan Kualitas Sayuran Dataran Rendah di Kabupaten Sidoarjo - Sulthan Disky Maulana; R. Achmad Djazuli; Resya Nurdyawati (CV.ITTC INDONESIA, 2026)
This study analyzes the adoption of Integrated Pest Management (IPM) technology in lowland vegetable farming in Sidoarjo Regency using a mixed methods approach involving 840 farmers in five central sub-districts selected through stratified random sampling. Data analysis employed logistic regression, Propensity Score Matching (PSM) with nearest neighbor method, and laboratory analysis. Results indicate a low IPM adoption rate of 39.3%, with 25.8% partial adopters and 13.5% complete adopters. The most adopted component is cultural practices (73.8%), while the least adopted is economic threshold application (14.2%). Significant determinants include education level (OR=1.091), Farmer Field School participation (OR=4.288), IPM input access (OR=2.545), and neighbor adoption rates (OR=8.914). PSM analysis showed IPM adoption significantly increased technical efficiency (DEA score: 0.785 vs 0.731, p=0.010), reduced pesticide use by 23% (p<0.001), and increased net profit by Rp 5.3 million/ha (p=0.002). Product quality from IPM adopters was superior with 67% reduction in pesticide residues, higher nutritional content, and an 8.4% price premium. Adoption sustainability reached 71.8% after two years. A total investment of Rp 66.5 billion is recommended to achieve a 75% adoption target within five years.